Molecular Mechanism of Double-Displacement Retaining β‑Kdo Glycosyltransferase WbbB - Rao, Deming; Zhu, Lin; Liu, Weiqiong; Guo, Zhiyong (The journal of physical chemistry. B, 2024)
Glycosyltransferases (GTs) are pivotal enzymes involved in glycosidic bond synthesis, which can lead to either retention or inversion of the glycosyl moiety’s anomeric configuration. However, the catalytic mechanism for retaining GTs remains a subject of controversy. In this study, we employ MD and QM/MM metadynamics to investigate the double-displacement catalytic mechanism of the retaining β-Kdo transferase WbbB. Our findings demonstrate that the nucleophile Asp232 initiates the reaction by attacking the sugar ring containing a carboxylate at the anomeric position, forming a covalent adduct. Subsequently, the adduct undergoes a rotational rearrangement, ensuring proper orientation of the anomeric carbon for the acceptor substrate. In the second step, Glu158 acts as the catalytic base to abstract the proton of the acceptor substrate to complete the transglycosylation reaction. Notably, His265 does not function as the anticipated catalytic acid; instead, it stabilizes the phosphate group through H-bonding interactions. Our simulations support the double-displacement mechanism implicated from the crystallographic studies of WbbB. This mechanism deviates from the common S N i-type and retaining glycoside hydrolase mechanisms, thereby expanding our understanding of GT catalytic mechanisms.